2018
DOI: 10.5812/jjnpp.60426
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of In vivo Antimalarial Activities of leaves of Moringa oleifera against Plasmodium berghei in Mice

Abstract: Background: In addition to resistance against drugs, no new drugs have reached the market during the last decade for malaria treatment. This implies the urgent need to search for new drugs from different sources. Medicinal plants are one of such sources for novel drugs. Therefore, the aim of the current study was to investigate antimalarial activity of crude extract of leaves of Moringa oleifera Lam (Moringaceae) in Plasmodium berghei in a mice model. Methods:The acute toxicity test was used as per standard gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 15 publications
3
13
0
2
Order By: Relevance
“…Many plant species used for the management of malaria have been specified within ethnobotanical studies conducted in various regions of Ethiopia [11][12][13][14]. In addition, the results of various animal experiments on different types of traditional medicinal plants showed promising antimalarial activity [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Many plant species used for the management of malaria have been specified within ethnobotanical studies conducted in various regions of Ethiopia [11][12][13][14]. In addition, the results of various animal experiments on different types of traditional medicinal plants showed promising antimalarial activity [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…(Moringaceae) is commonly known as moringa or drumstick. It has antihypertensive, antidiabetic [19], antibacterial [20], antinociceptive, larvicidal, antifungal, antiinflammatory, analgesic, antimalarial [21,22] and antisickling [23] activities. The plant has been reported to contain phenols (glucosinolates and isothiocyanates), flavonoids, alkaloids, glycosides, amino acids, carotenoids, vitamins and sterols [24].…”
Section: Introductionmentioning
confidence: 99%
“…The alkaloids, phenols and saponins identified in methanolic extracts of Achyranthes aspera shoot in the study are in-line with the findings reported in a studies conducted by Sharma, Chandhary (2015) and Tiwari et al (2018) on methanolic and ethanolic leaf extract of Achyranthes aspera. Alkaloids were reported to exert antimalarial activity by blocking protein synthesis in P. falciparum (Liu et al, 2017), likewise phenols and tannins are reported to exhibit antimalarial activities (Soh et al, 2012). Phenols have been reported in several plants as the major pharmacological contributors, thereby suggesting that same chemical compounds might be likely the key player for the vast medicinal potentials of Achyranthes aspera.…”
Section: Discussionmentioning
confidence: 99%
“…Parasitemia was calculated by using the formula below: % Parasiteamia = x100 (12). The mean survival time for each group was determined by finding the average survival time (days) of mice (post-inoculation) over a period of 30 days (D0-D29) as a principle compound that prolonged survival time beyond 12 days is regarded as active (Ural et al, 2014;Mulisa et al, 2018).…”
Section: Plant Extractionmentioning
confidence: 99%